Blue lights. Series 3 [videorecording (DVD)] - Lawn, Declan; Patterson, Adam, 1982-; Braniff, Nathan; Brooke, Sian, 1980-; Devlin, Katherine (BBC Studios, 2026)
As Grace, Annie and Tommy complete their probationary period, they face emotional and professional challenges within a complex world where moral lines are blurred. Grace grows exasperated by the limits of the job. But when she encounters a former social work client enslaved by a criminal gang, she discovers a web of exploitation. Annie has settled into her role but at the cost of her family and faces the prospect of a lonely future. Meanwhile, Tommy excels professionally but his relationships with partner Shane and girlfriend Aisling threaten his career. As the recruits confront a world of drug dealing, child abuse and white-collar crime, the trio must reconcile themselves with the realities of modern-day policing.